Following the star: Inflorescence heliotropism - Serrano, Alejandro M.; Arana, María Veronica; Vanhaelewyn, Lucas; Ballare, Carlos Luis; Van Der Straeten, Dominique; Vandenbussche, Filip (Elsevier, 2019)
Plant movements in response to directional solar radiation, known as “heliotropism” are frequently observed in nature. Although there is a considerable amount of literature on these movements in vegetative organs, knowledge about heliotropic responses in flowers and inflorescences is relatively limited. Here we comprehensively review studies on this topic, profile the diversity of responses encompassed under the term “heliotropism” and propose a conceptual framework for their classification. In addition, we discuss the mechanisms underlying different types of heliotropism in two species commonly used as model systems: Arabidopsis and sunflower. Finally, the ecological consequences of floral heliotropism are elaborated with an emphasis on the effects on plant reproductive success, and the potential agricultural implications of manipulating heliotropic responses are addressed as well. We conclude that inflorescence heliotropism appears conserved in many plant species that depend on pollinators, and consists of an auxin dependent response to solar radiation.